2022
DOI: 10.1212/nxg.0000000000000677
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic ATOH1 Gene Variant in Siblings With Pontocerebellar Hypoplasia, Developmental Delay, and Hearing Loss

Abstract: Background and ObjectivesTo report on the novel association of biallelic variant in atonal basic helix-loop-helix transcription factor 1 (ATOH1) gene and pontocerebellar hypoplasia (PCH), severe global developmental delay, intellectual disability, and hearing loss in a family with 2 affected siblings.MethodsA detailed clinical assessment and exome sequencing of peripheral blood sample were performed. Segregation analysis with Sanger sequencing and structural modeling of the variant was performed to support the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…S1). These data suggested that partial loss of function of Atoh1 not only leads to delayed development of PN but also leads to PN hypoplasia in mice reminiscent of the malformation of the PN in patients with ATOH1 missense variant ( 22 ). Together, these data reinforced the importance of Atoh1 in PN development and demonstrated that Atoh1 hypomorphic allele could provide a useful mouse model to dissect the functions of Atoh1 during PN development.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…S1). These data suggested that partial loss of function of Atoh1 not only leads to delayed development of PN but also leads to PN hypoplasia in mice reminiscent of the malformation of the PN in patients with ATOH1 missense variant ( 22 ). Together, these data reinforced the importance of Atoh1 in PN development and demonstrated that Atoh1 hypomorphic allele could provide a useful mouse model to dissect the functions of Atoh1 during PN development.…”
Section: Resultsmentioning
confidence: 95%
“…In the hindbrain, Atoh1 -lineage neurons contribute to many key components of the proprioceptive pathway, including the PN ( 9 , 21 ). A recent report implicated a homozygous missense variant in ATOH1 in two human patients with global developmental delay, motor function deficits, pontocerebellar hypoplasia, and hearing loss ( 22 ). It is thus of great interest and clinical relevance to understand how Atoh1 shapes proper PN development.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased proliferation of GCPs in pigs was associated with reduced expression of cell-cycle promoting cyclins and the Atoh1 and Jag1 genes ( Iskusnykh et al, 2018 ). The Atoh1 transcription factor is critical for the expansion of GCPs, and the secreted mitogen jagged canonical notch ligand 1 (Jag1) promotes the proliferation of GCPs in the mouse ( Solecki et al, 2001 ; Flora et al, 2009 ; Klisch et al, 2011 ; Višnjar et al, 2022 ). Interestingly, supplementation of ex vivo cerebellar slices from preterm pigs with recombinant Jag1 protein rescued GCP proliferation, further supporting the role of Jag1 as an essential mediator of the preterm cerebellar hypoplasia phenotype ( Iskusnykh et al, 2018 ).…”
Section: The Impact Of Preterm Birth On Different Cerebellar Cell Typesmentioning
confidence: 99%